2016
DOI: 10.1126/science.aaf4951
|View full text |Cite
|
Sign up to set email alerts
|

Northeastern North America as a potential refugium for boreal forests in a warming climate

Abstract: High precipitation in boreal northeastern North America could help forests withstand the expected temperature-driven increase in evaporative demand, but definitive evidence is lacking. Using a network of tree-ring collections from 16,450 stands across 583,000 km(2) of boreal forests in Québec, Canada, we observe a latitudinal shift in the correlation of black spruce growth with temperature and reduced precipitation, from negative south of 49°N to largely positive to the north of that latitude. Our results sugg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

12
126
1
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 149 publications
(140 citation statements)
references
References 45 publications
12
126
1
1
Order By: Relevance
“…. Our findings are further supported by studies that have demonstrated temperature-driven growth increases in northern conifer populations using both dendrochronological223435 and satellite-based3637 lines of evidence; though these temperature-driven responses may be overshadowed by water limitations in some boreal regions73839.…”
Section: Discussionsupporting
confidence: 85%
See 1 more Smart Citation
“…. Our findings are further supported by studies that have demonstrated temperature-driven growth increases in northern conifer populations using both dendrochronological223435 and satellite-based3637 lines of evidence; though these temperature-driven responses may be overshadowed by water limitations in some boreal regions73839.…”
Section: Discussionsupporting
confidence: 85%
“…For example, changes in climate extremes (e.g., drought), disturbance regimes (e.g., insects and fire), and water-use efficiency due to CO 2 fertilization have been identified as factors shaping the structure, composition, and productivity of future forests78192021. While these factors add considerable complexity to growth projections, we feel there is significant value in establishing a baseline expectation regarding tree response to warming temperature – a key driver of growth in northern forests22.…”
Section: Discussionmentioning
confidence: 95%
“…The forests studied here, where MAP can exceed more interiorcontinental sites by up to 1000 mm, receive annual precipitation that exceeds evaporative demand (Figure 2), an important feature impacting the balance of net C fixation relative to respiration (Dunn et al, 2006). Our results suggest that in regions where forest productivity is predicted to increase under future climate scenarios (Charney et al, 2016;D'Orangeville et al, 2016), soil C inputs can keep pace with the increased losses associated with warming. Experimental warming in temperate forests has revealed initial net losses of C from soils that were ameliorated by gains in plant productivity in response to warming (Melillo et al, 2011).…”
Section: Resultsmentioning
confidence: 59%
“…The increases in biomass and forest productivity along with temperature increases have been detected in many forest types [48,49], and unprecedented tree growth in bristlecone pine was found in the highest elevations of western North America [48]. Forest productivity and biomass are expected to increase with the increased tree growth in these temperature-limited systems [51] and our study region might act as a climatic refugium with future warming [52]. However, our modeling effort produced declines in tree growth with temperature after ca.…”
Section: Discussionmentioning
confidence: 65%